Brain-Gut Interactions in Inflammatory Bowel Disease: Mechanisms of Anorexia in Animal Models of Experimental Colitis - Harvey P Weingarten (Canadian Journal of Gastroenterology)
Physiological processes within the bowel are influenced constantly by signals from other organs, primarily the brain. The mechanisms by which inflammation of the gastrointestinal tract results in anorexia are unknown. Understanding how the inflammation-related signals in the periphery are communicated to the central nervous system and activate cytokine production in the brain remains an enormous challenge. Elucidation of these gut-brain communication mechanisms is essential to the development of appropriate and efficacious treatments for the eating and weight disturbances associated with inflammatory bowel disease.